MODEL DISCOVERY LEARNING DALAM KETERAMPILAN MENULIS TEKS EKSPOSISI DAN BERPIKIR KRITIS : Eksperimen Kuasi terhadap Siswa Kelas VII SMPN 1 Nagreg - Oktaviani, Pusparani (2015)
Penelitianinidilatarbelakangirendahnyakemampuansiswadalammenulistekseksposisidankemampuanberpikirkritis.Penelitianinibertujuanuntukmengetahuibagaimanaprofilpembelajaranmenuliseksposisidankemampuanberpikirkritissebelumdiberikanperlakuan model discovery learningpadasiswakelas VII SMPN 1 Nagreg, bagaimanakahpenerapan model Discovery Learningterhadapkemampuanmenulistekseksposisidanberpikirkritispadasiswakelas VII SMPN 1 Nagreg, apakahterdapatperbedaan yang signifikanpembelajaranmenulistekseksposisidanberpikirkritis di kelaseksperimendankelaskontrol. Jenispenelitianiniadalaheksperimenkuasidengandesain prates-pascatesdengankelompokeksperimendankontrol (nonequivalent control group design).Populasidalampenelitianiniadalahseluruhsiswakelas VII SMPN 1 Nagregdenganmenggunakanduakelassebagaisampeldarisepuluhkelas yang tersedia.Kelaseksperimenmendapatperlakuan model discovery learningdankelaskontrolmendapatperlakuanterlangsungataumetodeceramah. Data utamadalampenelitianiniberupahasiltulisantekseksposisisiswapadatesawaldantesakhir, sedangkan data pendukungberupatemuandalam proses pembelajaran. Pengumpulan data dilakukanmelaluitekniktesdanobservasi. Untukmelihatefektivitas model discovery learning, dilakukanpengujianmenggunakanuji-t dengantarafsignifikan 0, 05 setelahujiprasyaratterpenuhi. Hasilpenelitiandianalisismenggunakanmicrosoft excel dan program SPSS versi 19. Berdasarkanhasilpenelitian, diketahuibahwaketerampilanmenulistekseksposisidanketerampilanberpikirkritissiswamasihrendah.Model discovery learning diterapkanmelaluilangkah-langkah, yaknistimulasi, identifikasimasalah, pengumpulan data, pengolahan data, pembuktiandangeneralisasi.Hasilperhitunganstatistikmenunjukkanterdapatperbedaandalamketerampilanmenulistekseksposisidanberpikirkritisdenganmenggunakan model discovery learningdanmetodeterlangsung.Hasilpenelitianmenunjukkanterdapatperbedaan yang signifikandalamketerampilanmenulistekseksposisidanberpikirkritis.Hasilpengujiandiperolehbahwauntukhipotesispertama p-value menunjukkanangka 0.000 yang artinyabahwa p-value <0.05 sehingga H0ditolakdandapatdisimpulkanadaperbedaannilaimenuliseksposisipadakelaskontroldankelaseksperimen.Hasilpengujiandiperolehbahwa p-value menunjukkanangka 0.000 yang artinyabahwa p-value <0.05 sehingga H0ditolakdandapatdisimpulkanadaperbedaannilaiberpikirkritispadakelaskontroldankelaseksperimen.Dengandemikian, model discovery learning efektifmeningkatkanketerampilanmenulistekseksposisidanberpikirkritis. MODEL DISCOVERY LEARNING TO IMPROVE SKILLS AND WRITE TEXT exposition CRITICAL THINKING Abstract: This research is motivated low ability students in writing the text exposition and critical thinking skills. This study aims to determine how the profile of learning to write exposition and critical thinking skills before being given treatment model of discovery learning in class VII SMPN 1 Nagreg, how the implementation model of Discovery Learning in the ability to write text exposition and critical thinking in class VII SMPN 1 Nagreg, whether there are significant differences of learning to write text exposition and critical thinking in the experimental class and control class. This research is a quasi experimental design with pre-test-post-test with the experimental and control groups (nonequivalent control group). The population in this study were all students of class VII SMPN 1 Nagreg using two classes as samples from ten classes available. Class experimental model of discovery learning treated and control treated class or lecture. The main data in this study is the result of a text written exposition of students at the beginning of the test and final test, while supporting data in the form of the findings in the learning process. Data collected through tests and observation techniques. To see the effectiveness of the model of discovery learning, testing performed using t-test with a significant level of 0, 05, after the test prerequisites are met. Results of the study were analyzed using Microsoft Excel and SPSS version 19. Based on this research, it is known that the exposition text writing skills and critical thinking skills of students is still low. Discovery learning model is implemented through measures, ie stimulation, problem identification, data collection, data processing, verification and generalization. Results of statistical calculation shows that there are differences in the exposition text writing skills and critical thinking by using discovery learning models and methods terlangsung. The results showed there were significant differences in the exposition text writing skills and critical thinking. The test results showed that for the first hypothesis p-value indicates the number 0.000, which means that the p-value of <0.05 so that H0 is rejected and it can be concluded there is a difference value write exposition on the control class and experimental class. The test results showed that p-value indicates the number 0.000, which means that the p-value of <0.05 so that H0 is rejected and concluded no difference in the value of critical thinking in the control class and experimental class. Thus, the model of discovery learning effectively improve writing skills and critical thinking exposition text.